PERILAKU BERBAHASA ANAK DARI KELUARGA UTUH DAN KELUARGA TIDAK UTUH DI KOTA MAKASSAR: STUDI KASUS - Indarwati Indarwati (Universitas 17 Agustus 1945 Surabaya, 2017)
ABSTRACT. A child acquired a language in the family which is the first world for them. This research aims at explaining the language behavior of children from the intact family and the children from the broken family in Makassar. The research is a qualitative research by applying psycho-sociolinguistics approach. The data of the research were oral interviews through observation, recording, and note taking. The samples were selected by applying purposive sampling. The data were analyzed descriptively using Milles and Huberman model. The results of the research showed that the language behavior of the children from the intact family is more spoiled, outspoken and polite. Meanwhile children from broken home family show independent, quiet and introverted, less polite and sensitive behavior. Keywords: children's language, family, language behavior